Corporate managers and their potential younger successors: An examination of their values - Katharina Katja Mihelic; Bogdan Lipicnik (Journal for East European Management Studies, 2010)
Human values are individual characteristics that vary in importance and serve as guiding principles in a person's life. The purpose of this paper is to identify the values held today by Slovenian managers and students and contributes to the few studies that have examined the influence of age on values. The exploratory study comprises 130 managers and 118 students majoring in management. The managers highly value health, family happiness, honesty, freedom and wisdom, whereas the students perceive as the most important good friends, knowing oneself, health, freedom, loyalty and family happiness. – – Menschliche Werte sind individuelle Merkmale, die sich nach ihrer Wichtigkeit unterscheiden und als Leitprinzipien im Lebens einer Person dienen. Der Zweck dieses Artikels ist, die Werte von slowenischen Führungskräften und Studenten zu identifizieren und einen Beitrag zu leisten zur Erforschung des Einflusses des Alters auf Werte. Diese explorative Studie umfasst 130 Führungskräfte und 118 Studenten mit Studienschwerpunkt Management. Die Führungskräfte schätzen als Gesundheit, Familienglück, Ehrlichkeit, Freiheit und Weisheit am höchsten ein, die Studenten vor allem gute Freunde, Selbstverwirklichung, Gesundheit, Freiheit, Loyalität und Familienglück.
Keywords: 650; values; behaviour; age; managers; students; Slovenia